Pharmacological approaches to the prevention of type 2 diabetes mellitus - Majety, Priyanka; Lozada Orquera, Faustina Alejandra; Edem, Dinesh; Hamdy, Osama (Frontiers in Endocrinology, 2023)
About 1 in 10 adults worldwide are estimated to have diabetes mellitus. They are at risk of developing life-threatening complications resulting in reduced quality of life, increased mortality and higher healthcare costs. The ability to prevent or delay type 2 diabetes mellitus (T2DM) by modifying some of its risk factors has been hypothesized for decades. The long and often gradual time-course of increasing dysglycemia prior to diabetes diagnosis suggests that interventions during that period could be effective in preventing T2DM. In addition to lifestyle modifications, certain drugs prevent or slow development of hyperglycemia. Recently, drugs used for obesity management were shown to prevent T2DM. In this review, we discuss various pharmacotherapeutic options for preventing T2DM.